Lactylation modification in cancer: mechanisms, functions, and therapeutic strategies - Mengqi Lv; Yefei Huang; Yansu Chen; Kun Ding (Experimental Hematology & Oncology)
Abstract Cancer remains the leading cause of mortality worldwide, and the emergence of drug resistance has made the identification of new therapeutic targets imperative. Lactate, traditionally viewed as a byproduct of glycolysis with limited ATP-producing capacity, has recently gained recognition as a critical signaling molecule. It plays a key role not only in cancer cell metabolism but also in shaping the tumor microenvironment (TME). Histone lysine lactylation, a newly identified post-translational modification, has been shown to influence a range of cellular processes in cancer. Current research focuses on the mechanisms and functions of histone lactylation in cancer, including its role in gene expression regulation, signal transduction, and protein synthesis. However, despite these advancements, there are still plenty of barriers in the quest to unravel the mechanisms of lactylation modification. The emergence of single-cell and spatial transcriptomics may offer valuable insights for selecting targets. This review provides a comprehensive summary of the mechanisms and the applications of lactylation modification in clinical settings. Through a detailed analysis, we identify the key challenges and limitations that exist in the current research landscape. These insights lay the groundwork for future studies by highlighting promising research directions.